A study of silicon p-n structures with mono- and multifacial photosensitive surfaces - Mirzaalimov, A.; Gulomov, J.; Aliev, R.; Mirzaalimov, N.; Aliev, S. (Nauchno-tekhnicheskiĭ vestnik informat͡s︡ionnykh tekhnologiĭ, mekhaniki i optiki, 2024)
Increase in the efficiency and reduction of silicon consumption in production of solar cells are relevant problems. Designing two and three facial solar cells can be seen as a solution for such tasks. Compared to usual SC, the output power of two and three facial solar cells exceeds by 1.72 times by 2.81 times, respectively. Illumination of solar cells with high intensity light makes the temperature of its heating an important characteristic. Therefore, the paper investigates the influence of temperature on properties of multifacial solar cells. We defined the nature of change of temperature coefficients for the main photovoltaic parameters that are inherent to silicon solar cells under various (one, two and three facial) conditions of lighting. Temperature coefficients of three facial solar cells are 2.52·10–3 V/K for open circuit voltage and 1.8·10–3 K–1 for fill factor of I-V. At temperature change of SC from 300 K to 350 K, the density of short circuit current decreases only by 4 %.